2019
DOI: 10.35940/ijrte.b1057.0982s919
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of Teamwork in Work Engagement among Gen Y-A Conceptual Framework

Abstract: As the older generation is retiring from the workforce, it became a concern for many organizations on ways to manage the new generation who is flowing into the current workforce. This new generation is known as Gen Y. This generation workforce often linked to job hopping and their loyalty towards the organization is being questioned by researchers as many organizations are experiencing a high level of attrition among them. This study investigated teamwork as a critical success factor of work engagement among G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
1
1
Order By: Relevance
“…The results for hypothesis two to the effect that diversity management programmes have a significant influence on the workplace engagement of academic staff showed that the hypothesis was rejected. This finding was inconsistent with the findings of previous scholars (Alshaabani et al, 2021;Ganji et al, 2021;Gupta & Gomathi, 2022;Jayashree et al, 2019;Kang & Sung, 2017;Mbhele & De Beer, 2021;Mistry et al, 2021;Ravikumar, 2013;Verčič & Men, 2023), who indicated that employee engagement was positively influenced by diversity management programmes. However, the diversity programmes had a significant influence on work engagement because the descriptive results revealed that the programmes were given less prominence in the university.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The results for hypothesis two to the effect that diversity management programmes have a significant influence on the workplace engagement of academic staff showed that the hypothesis was rejected. This finding was inconsistent with the findings of previous scholars (Alshaabani et al, 2021;Ganji et al, 2021;Gupta & Gomathi, 2022;Jayashree et al, 2019;Kang & Sung, 2017;Mbhele & De Beer, 2021;Mistry et al, 2021;Ravikumar, 2013;Verčič & Men, 2023), who indicated that employee engagement was positively influenced by diversity management programmes. However, the diversity programmes had a significant influence on work engagement because the descriptive results revealed that the programmes were given less prominence in the university.…”
Section: Discussioncontrasting
confidence: 96%
“…On their part, Verčič and Men (2023), in a study involving workers in Croatian firms, reported that internal communication had a significant influence on employee engagement. In a review, Jayashree et al (2019) established the existence of a significant positive relationship between team-building teamwork programmes and work engagement. Finally, in a study involving employees of small and medium enterprises in India, Ravikumar (2013) found that teamwork had a meaningful positive association with employee engagement.…”
Section: Diversity Managementmentioning
confidence: 99%
“…Furthermore, Indian cohorts rated team climate and team leader humility higher. The findings stand in support of the existing literature, as GenY prefers a healthy work climate, where the engagement from team members could be enhanced to attain the outcome (Jayashree et al. , 2019), and a flexible work environment and teamwork motivates them (Camp et al.…”
Section: Discussionsupporting
confidence: 84%